(untitled) (Palíndromo, 2021)
This essay is based on the presentation of the series of photographs made through video calls “Here e There”. The intention of this poetic and text is to analyze the perception of a virtual mode of existence. The study proposes a critical analysis of the society increasingly dependent on screens and images and the role of technology in this context.